Understanding sustainable livelihood strategies of female-headed households: the case of Renosterberg Municipality, Pixley ka Seme District, Northern Cape - Phuzi, Bonakele (University of the Free State, 2021)
The population of female-headed households in South Africa has significantly risen. The Statistics SA General House Survey (GHS) of 2020 revealed an estimate of 7.2 million or 41.9 percent of these households are headed by women, an increase from 41.8 percent estimated in the 2019 GHS. Studies agree that FHHs are exposed to different livelihoods challenges and experiences. Through a qualitative interview with 22 female participants, this study engaged in an in-depth exploration to understand the challenges faced by female-headed households, investigate the existing livelihood strategies of FHHs, and reflect on relevant mechanisms that respond to difficulties and pressures experienced by female heads. This study utilised a sustainable livelihood approach to focus on a typical South African municipal setting of Renosterberg Local Municipality to explore the challenges and understand the livelihoods strategies used by females heading households to sustain their families. The study results revealed that a combination of factors such as deaths of husbands, husbands leaving families, unemployment and sickness of husbands, deaths of parents and females never marrying contribute to FHHs in Renosterberg Local Municipality. The study established that child support grants and part-time employment are the most significant sources of income in FHHs, and they are constantly experiencing shortages of money, food, clothing and school supplies. The study found that most FHHs are unemployed and often rely on informal jobs and rely on life skills such as hairdressing to earn money to feed their families. Despite these identified challenges, the study realised those female-headed households are eager to improve themselves and expand their sources of income through obtaining skills and further qualifications such as early childhood development certificates, computer training and completing their matric. Others are highly involved in community programmes that enhance their social skills and give them access to different programmes that earn them an income. This study established that FHHs have various coping mechanisms they rely on to sustain their livelihoods. Therefore, the study reflected on the need for more government mechanisms to enhance the skills capacity of female-headed households, increase their employment rate and expand their income support. Therefore, this study explored and discussed the sustainable livelihoods and the survival strategies of FHHs in Renosterberg Local Municipality.
Dissertation (MDS (Development Studies))--University of the Free State, 2021
Keywords: Female-headed household; Sustainable livelihood; Survival strategies